PENANANAMAN NILAI KEDISIPLINAN M PENANANAMAN NILAI KEDISIPLINAN MELALUI METODE BERCERITA UNTUK ANAK USIA DINI: PENANANAMAN NILAI KEDISIPLINAN MELALUI METODE BERCERITA UNTUK ANAK USIA DINI - Nur Handayani, Iys; Isnaningsih, Anti (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2023)
This study aims to determine the application of inculcating the value of discipline through the storytelling method for early childhood. This research belongs to the type of qualitative research and was carried out at PAUD IT Harapan Bunda Klaten. The objects of this study were the teachers and students of group A and group B. The data collection techniques used were observation, interviews, and documentation. While the technique of checking the validity of the data uses source triangulation, technical triangulation, and time triangulation. The result of this research is the inculcation of the value of discipline through the storytelling method at PAUD IT Harapan Bunda Klaten, namely through learning activities and early morning activities. Starting with preparing the RPPH and preparing learning tools and materials. Furthermore, the teacher applies the inculcation of discipline values through the storytelling method during learning. Instilling the value of discipline with the theme of experiences and stories of disciplined children. The teacher uses media such as hand puppets, finger puppets and picture story books. With the storytelling method, children can apply the environmental discipline values of PAUD IT Harapan Bunda Klaten. The values of discipline applied at PAUD IT Harapan Bunda Klaten are as follows: a) Children wear uniforms according to a predetermined schedule; b) Children arrive on time/not late; c) Children queue when entering class, taking food and doing ablution; c) Children throw garbage in the trash; d) The child puts the shoes on the shoe rack; e) Children tidy up toys after playing; e) Children obey the rules in school and class.